2018
DOI: 10.3906/sag-1507-120
|View full text |Cite
|
Sign up to set email alerts
|

HIV infection and poor renal outcomes following noncardiac surgery

Abstract: Background/aim: The relevance of HIV infection in perioperative renal risk stratification remains unclear. This research sought to investigate the impact of HIV infection, as well as other established preoperative risk factors for poor perioperative renal outcome (PPRO), in a population of 565,225 adult noncardiac surgery patients whose data were obtained from the 2009-2011 California State Inpatient Database. Materials and methods: HIV status, established preoperative risk factors, and the study outcome (PPRO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…However, with advancements in ART, HIV infection is now becoming a controllable chronic disease (20,21). Some recent studies revealed that postoperative complication rates in patients with well-controlled HIV infections were comparable to those in HIV-negative patients (15,(22)(23)(24)(25)(26). CD4+ lymphocyte status is one of the indicators of HIV infection status (27,28), and various reports have revealed that a low CD4+ lymphocyte count (especially < 200 cells/μL) was associated with a significant increase in postoperative complications (12,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…However, with advancements in ART, HIV infection is now becoming a controllable chronic disease (20,21). Some recent studies revealed that postoperative complication rates in patients with well-controlled HIV infections were comparable to those in HIV-negative patients (15,(22)(23)(24)(25)(26). CD4+ lymphocyte status is one of the indicators of HIV infection status (27,28), and various reports have revealed that a low CD4+ lymphocyte count (especially < 200 cells/μL) was associated with a significant increase in postoperative complications (12,29,30).…”
Section: Discussionmentioning
confidence: 99%